Study on the long-hole raising technique using one blast based on vertical crater retreat multiple deck shots - Liu, K.; Yang, J.; Li, X.; Hao, Hong; Li, Q.; Liu, Z.; Wang, C. (Pergamon, 2018)
Backfilling inaccessible cavity through raise can provide underground support for the active open-pit operations and the raise must be taken down in a single blast for safety reasons. Conventional raising techniques are not economically and technically feasible, and the maximum advance depth in one blast is limited. In this paper, small-scale crater tests were carried out in a site with cavities and field blasting test data were measured and evaluated to obtain the basic data for raise-scale blast designs. The raising design parameters with 250-mm hole diameter, including charge weight and height for each slice, slice height, hole spacing and delay interval, were derived. A scheme of multiple deck blasting based on vertical crater retreat (VCR) drop-raising method was designed for an abandoned cavity with 30-m cover. The lower 12-m cover was first blasted to investigate the practical blast performance. Charging and timing patterns were adjusted accordingly and the left 18-m cover was successfully opened up. Through raising tests, it is shown that the advantage of two available free surfaces up and down should be maximized, and smaller slice height and alternate initiation sequence are benefit for raising extension. A numerical model is then developed and it is calibrated against the 12-m raising test. By combining the calibrated numerical model with the raising test results, the effects of hole layout and in-slice delay are examined. It is shown that circular pattern and in-slice delay are positive for multiple-deck raising blast. Based on the foregoing analysis, the hole layout, charging and timing patterns are optimized. The optimized scheme was applied to field raising blast and a 32-m raise was successfully excavated in one blast.